Pam's pictures - Foster, John ([Oxford], Oxford University Press, 1999)
Fitting the requirements of the National Literacy Strategy, National Curriculum in England and Wales, English Language 5-14 in Scotland, and Common Curriculum in Northern Ireland, this work guides pupils through the skills associated with learning to read and write with literary styles within the genres of fiction, non-fiction, and others.